Advanced Technology of Waste Treatment - Vollprecht, Daniel; Sarc, Renato (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The protection of human health and the environment (representing the main reason for waste management), as well as the sustainable use of natural resources, requires chemical, biological, physical and thermal treatment of wastes. This refers to the conditioning (e.g., drying, washing, comminution, rotting, stabilization, neutralization, agglomeration, homogenization), conversion (e.g., incineration, pyrolysis, gasification, dissolution, evaporation), and separation (classification, direct and indirect (i.e., sensor-based) sorting) of all types of wastes to follow the principles of the waste hierarchy (i.e., prevention (not addressed by this issue), preparation for re-use, recycling, other recovery, and disposal). Longstanding challenges include the increase of yield and purity of recyclable fractions and the sustainable removal or destruction of contaminants from the circular economy.This Special Issue on "Advanced Technology of Waste Treatment" of Processes collects high-quality research studies addressing challenges on the broad area of chemical, biological, physical and thermal treatment of wastes.